Corrosion resistance of modified YSZ coatings subjected to CMAS attacks. (3rd April 2022) - Wang, Zhe; Zhang, Jingjing; Han, Shenghui; Liu, Jingxiao
ABSTRACT: The deterioration of thermal barrier coatings in reaction engines due to Ca–Mg-Al–Si (CMAS) attacks has been an important issue in recent years. Al2 O3 –20 wt-% TiO2 (AT) powder was mechanically doped into yttria-stabilized zirconia (YSZ). The corresponding coatings were fabricated using APS to modify the CMAS corrosion resistance. The corrosion-induced microstructure evolution and the composition development in the YSZ and AT-YSZ coatings were investigated. The AT-YSZ coating contained smaller voids and fewer cracks with a much more obvious laminated structure in contrast with the YSZ coatings. After CMAS attack, the YSZ coating flaked off, while the AT-YSZ coating was strongly bonded to the substrate. Phases from tetragonal (t'-ZrO2 ) to monoclinic (m-ZrO2 ) were detected, while the MgAl2 O4 spinel and gehlenite Ca2 Al2 Si2 O8 phases were formed after the CMAS corrosion. AT20 exists independently in the AT-YSZ coating, which readily causes Al2 O3 to accumulate in the CMAS and effectively arrests its infiltration.